Molibden Katkılı Elmas-benzeri Karbon Filmlerin Üretimi, Karakterizasyonu Ve Tribolojik Özellikleri - Alp, Emre (Fen Bilimleri Enstitüsü, 2014)
Karbon temelli kaplamalar birçok bilim dalına konu olmakta ve endüstriyel olarak kullanılmaktadır. Karbon doğada bol bulunan ve endüstriyel anlamda ekonomik bir elementtir. Karbon temelli malzemeler, elmasta olduğu gibi yüksek sertlik ve termal iletkenlik gösterirken, grafitte yumuşak ve yağlayıcı özellik göstermektedir. Bunların yanında karbonun karbon nano tüp, fuleren, karbon-karbon kompozit camsı karbon ve karbon nano fiberler gibi allotropları vardır. Elmas benzeri karbon ince filmler yüksek sertlik, düşük sürtünme ve yüksek aşınma dirençlerinden dolayı katı yağlayıcı olarak tribolojik uygulamalarda kullanımı oldukça yaygındır. Elmas benzeri karbon filmler ilk olarak 1950’lerde Schmellenmeier tarafından keşfedilmiştir ancak Eisenberg ve Chabot’un 1970’lerde yaptıkları çalışmalar ile ilgi çekmiştir. Daha sonra ki yıllarda hakkında bir çok bilimsel yayın yapılmış ve patent alınmıştır. Elmas benzeri karbon filmlerin tribolojik uygulamalardaki performansı büyük oranda onun altlığa yapışma özelliğine bağlıdır. Silikon ve titanyum gibi karbür yapabilen altlıklara ve arakatman kullanılarak yapılan uygulamalarda yapışma mukavemeti iyidir. Elmas benzeri karbon filmlerin doğasından kaynaklanan yüksek basma gerilmeleri içermesi ve yüksek sıcaklıklarda faz değiştirmesi dezavantajlarındandır. Nano kristal yapılar ya da nano fazlar içeren elmas benzeri karbon filmler fiziksel ve kimyasal buhar biriktirme teknikleriyle zorlu şartlarda kullanım için üretilebilmektedir. Son yıllarda hibrit buhar biriktirme sistemlerinin geliştirilmesiyle elmas benzeri karbon filmlerin özelliklerinin daha kolay kontrol edilebilmesiyle endüstriyel uygulamalardaki dayanım gereklilikleri ve performansları arttırılmıştır. Metaller (Ti, Cu, W, Mo, Ta, Cr, Ni…), hafif elementler (B,Si, N, O, F) veya bunların kombinasyonlarıyla alaşımlanan ya da katkılanan elmas benzeri karbon filmlerin sertlik, iç gerilme, yapışma, tribolojik özellikleri, elektrik ve termal iletkenlikleri ve biyo-uyumlulukları değiştirilebilmektedir. Amorf yapı içerisine gömülen katkılandırılmış elementler matriks içerisinde tek bir faz olarak ya da ayrı bir ikincil faz olarak nano ölçeklerde oluşturulabiliyor. Bu nano kompozit ya da çok katmanlı filmler geliştirilmiş sertlik, tokluk ve yapışma özellikleriyle üstün aşınma dirençleri sergilemektedirler. Elmas benzeri karbon filmlere Nb, Ti, W ve Mo gibi karbür yapma afiniteleri yüksek metalik elementlerin katkılanması onun amorf matriks içerisinde nano kristal karbür taneleri olarak dağılmasına yol açmaktadır. Bu nano kompozit kaplamaların sertlik değerleri 30 Gpa’ ın üstüne çıkan değerler gösterebilmektedir. Hatta hidrojen içermeyen atmosferlerde üretilen elmas benzeri karbon ince filmlerin sertliklerinin neredeyse 90 GPa’ a kadar çıktığı belirtilmiştir. Elmas benzeri karbon filmlerin tribolojik uygulamalarda kullanımının çok büyük bir ilgi görmesinin nedeni yüksek sertlik ve yüksek kimyasal kararlılık göstermesiyle birlikte çok düşük sürtünme katsayısı ve aşınma katsayısı göstermesidir. Son yıllarda, elmas benzeri karbon yapıların tribolojik uygulamalarda kullanımı artan bir ivmeyle devam etmektedir. Bu çalışma, metan ve argon gaz ortamında yüksek vakum değerlerinde paslanmaz çelik altlık üzerine darbeli manyetik alanda sıçratma ve plazma destekli kimyasal buhar biriktirme hibrit yöntemiyle amorf karbon matriks içerisine molibden katkılamayı amaçlamaktadır. Metan-argon gaz karışımındaki argon miktarının değiştirilmesiyle amorf matriks içerisinde farklı molibden içerikleri oluşturulmuştur. Elmas benzeri karbon amorf matrikste artan oranda molibden katkısının oluşumu metan gazının kaplama ünitesine akış hızı sabit tutularak argon gazının kaplama ünitesine giriş hızı artırılarak yapılmıştır. Değişen molibden içeriğiyle matriks içerisinde oluşan nano-molibden karbür fazlarının aşınma ve sürtünme davranışlarına etkisi irdelenmiştir. Üretilen faklı molibden içerikli elmas benzeri karbon filmlerin yapısal ve kompozisyonel değerleri Raman spektrometresi, XRD ve EDS tekniklerini kullanan cihazların yardımıyla incelenirken sertlik ve tribolojik özellikleri mikrosertlik ve disk üzeri top aşınma cihazlarının yardımıyla incelenmiştir. Molibden katkılı elmas benzeri karbon filmlerin paslanmaz çelik altlığa yapışma özellikleri için kaplamalara çizik testi uygulanmıştır. Bunun yanında çizik testinin doğruluğunu pekiştirmek ve kaplamada oluşacak kırık tiplerine göre yorumlamak amacıyla Rockwell Testi uygulanmıştır. Bütün sonuçlar irdelendiğinde molibden katkısının kritik bir değere kadar elmas benzeri karbon kaplamaların sürtünme ve aşınma özellikleri makul bir değerdeyken molibden katkısının artmasıyla kaplamaların sürtünme ve aşınma özellikleri kötüleşmiştir.

Thin films whose thickness is typically less than several microns are produced by the deposition of individual atoms on any substrate. Historically, thin films have been used for about half a century in producing instrument hard coatings, optical coatings, thin-film batteries, electronic devices, photovoltaic devices, memory devices and decorative parts. Thin film technology is still being developed by a technological advancement since it is a key factor in the twenty-first century development of new materials such as nanometer materials and/or a man-made superlattices. Thin film materials are also suitable for minimization of toxic materials. Thin film processing also saves on energy consumption in production and is considered an environmentally benign material technology for the next century. Among all physical phenomena, friction perhaps is one of the greatest challenges for the industrial and scientific communities. Friction has a direct connection about to energy efficiency and environmental cleanliness of all moving mechanical systems. We rarely think about friction or appreciate the value of its importance in daily life. However, there is no doubt that it is a major cause of lost energy, and as well as hazardous emissions to our world. Consequently, the search for further reducing friction in engineering systems has real-life effects for not only conserving our limited energy resources, but also saving our planet from hazardous emissions. The friction between two solid surfaces in solid-state contact is the resistance to tangential motion of one surface over the other. In the field of tribology, the term friction coefficient is frequently used to describe the resistance to tangential motion. When the extent of physical and/or chemical interactions is extremely small or essentially absent, the surfaces can slide over one another without causing much friction. For this situation, the word “superlubricity” was first used by Motohisa Hirano. Historically, the earliest studies on superlubricity started in mid-1980s, but the real progress occurred during the 1990s. The abundance of raw material and the economic value of the material produced for engineering applications is the most important issue. When we look at from this point, carbon, which exists in more than 90% of all known substances, is one of the most abundant elements in our planet. Carbon has the largest number of allotropes, including diamond, white carbon, graphite, buckyballs, carbon nanotubes, and other forms of fullerenes. Besides these allotropes, there exist several more carbon-based non-crystalline materials, including carbon–carbon composites, bulk glassy carbons, and amorphous Diamond-like carbon films. DLC is the subject of this study because of its low friction property and well wear behaviour. Diamond-like carbon thin films was first reported in the early 1950s. However, base progress and systematic studies started in the 1970s. Over the years, diamond-like carbon films have attracted huge scientific and commercial interest mainly because of their superlow friction and wear, excellent optical, high chemical inertness aand dielectric properties. Especially, Diamond-like carbon films has attracted great interest in tribological applications due to their low friction and good wear baheviour. Unlike synthetic diamond films, the production of diamond-like carbon is rather easy and can be achieved over a broad range of deposition conditions and temperatures. Physical vapor deposition (PVD) and chemical vapor deposition (CVD) methods can be used to produce diamond-like carbon thin films on substrate materials which include metals, ceramics, and certain polymers. The carbonaceous precursors used and the deposition conditions, such as deposition temperature, gas pressure and applied bias voltage on substrate, strongly change the type of bonds (i.e., sp1 , sp2 , sp3 ) that hold carbon atoms together in diamond-like carbon thin films. If a hydrocarbon gas (such as methane, ethane or acetylene) is used as the carbon source, diamond-like carbon films may contain considerable amounts of hydrogen in their microstructures. These highly hydrogenated DLC films (containing more than 40 at.% hydrogen) can be relatively soft but exhibit some of the lowest friction and wear coefficients. Tribological behaviour of diamond-like carbon films strongly depends on test conditions. Friction coefficient of diamond like carbon films can vary in the wide range of 0,01-1 depending on test conditions. In recent years, many scientists in this field have invented more forms of DLC by incorporating certain elements; such as H, N, B, F, Mo, Ta, Ti, Cr, W, and S into their amorphous microstructures. Some of these films are extremely hard -as high as 90 GPa-, while others are rather soft but provide some of the lowest friction and wear coefficients. Diamond-like carbon coatings are often used to prevent wear due to its excellent tribological properties. Diamond-like carbon thin films are very resistant to abrasive and adhesive wear. These films are now used in too many industrial applications, such as metal cutting tools, razor blades, magnetic hard disks, critical engine parts and microelectromechanical systems. Recent investigations have provided special materials with hardness in the range of diamond. The most common compounds developed in hardness applications are basically nitrides, carbides and borides of groups IV, V and VI of the transition metals. TiN, TiC, TiCN, TiAlN, CrN and Al2O3 can be exemplary given such compounds. Diamond-like carbon , WC/C and MoS2 are adequate for tribological applications containing lubrication due to their excellent tribological properties. Both of nitrides and carbide particles embedded in diamond-like carbon have also been produced. The doping of diamond-like carbon with metallic elements leads to structures presenting carbide nanocrystals distributed within the amorphous diamond-like carbon matrix. Metal-containing diamond-like carbon (Me-DLC) films exhibit hardness values above 30 GPa. Alloyed diamond-like carbon coatings is an important category of diamond-like carbon characterized by the incorporation of different elements in their structure to accomplish improved properties in respect to pure diamond-like carbon films. Dopants elements and their combinations are added to modify their properties via controlling content and distribution of the dopant elements such as hardness, internal stress, adhesion, tribological properties, electrical conductivity or biocompatibility. In this study, molybdenum-containing diamond-like carbon films were deposited on stainless steel via hybrid system of pulsed magnetron sputtering (PVD) and plasma enhanced chemical vapour deposition (PECVD) in an argon and methane atmosphere. The aim of this study is to change molybdenum contents in the amorphous matrix of diamond-like carbon. Different molybdenum contents in the amorphous matrix was formed by changing amount of argon gas in the methane-argon gas mixture. Formed nano-molybdenum and nano-molybdenum carbide phases in the amorphous matrix by changing molybdenum contents has been investigated how effects of friction and wear behaviour become. The structure and composition of the molybdenum-containing diamond-like carbon films were characterized by Raman spectroscopy, X-ray diffractometry (XRD) and energy dispersive spectroscopy (EDS). Scratch test has been applied to determine its adhesive strength to substrate. Thin film hardness has been determined by ultra submicron hardness test. A ball-on-disc test was carried out to analyze the wear behavior and frictional properties of different molybdenum-containing diamond-like carbon films.
Production, Characterization And Tribological Properties Of Molybdenum Doped Diamond-like Carbon Films
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: ince film; elmas benzeri karbon; molibden; nano-kompozit; triboloji; thin films; diamond-like karbon; molybdenum; nano-composites; tribology